Analisis Peran Aktor dalam Implementasi Kebijakan Pembangunan Sanitasi di Kabupaten Probolinggo - Sandy, Oka Ferry (Badan Penerbitan Jurnal (BPJ) FIA-UB, 2020)
Implementation is an important stage that must be carried out after a policy is formulated. The implementation of sanitation policies in Probolinggo District has a high complexity with various problems because what will be changed is not only the physical building but also the knowledge and also the attitude of the people to behave in a clean and healthy life. The involvement of various parties is needed in helping to overcome these problems so that goals and objectives can be achieved. This study aims to identify, map and formulate the role of stakeholders in the implementation of sanitation development in Probolinggo Regency. Data collection was carried out through interviews, observations and documentation and then analyzed descriptively qualitatively. From the results of the study, 13 actors were involved in the implementation of sanitation development. Actors who are key players are BAPPEDA, Public Health Office , the Housing and Resettlement Zone Office, the Community and Village Empowerment Office, USAID IUWASH PLUS and the Village Government. Good coordination, synergy and communication are needed in the successful implementation.